Improving Students’ Learning Outcomes Through Cooperative Integrated Reading And Composition (CIRC) Model In Teaching Descriptive Text - Dewi Lestari Pardede; Monalisa Marta Siahaan; Irving Josafat Alexander; Gloria Sirait (Jurnal Ilmu Pendidikan dan Sosial, 2026)
This study aims to improve students’ learning outcomes in learning descriptive text through the Cooperative Integrated Reading and Composition (CIRC) learning model. The research was conducted using Classroom Action Research (CAR) consisting of two cycles. Each cycle includes planning, action, observation, and reflection stages. The participants of this study were 30 seventh-grade students of SMP Siloam Medan. Data were collected through learning outcome tests, observation sheets, and documentation. The results of the study show that the implementation of the CIRC model significantly improved students’ learning outcomes. In the first cycle, the percentage of students who achieved the minimum mastery criteria was 63%. After improvements in the second cycle, the mastery level increased to 86%. In addition, students' participation and collaboration during learning activities also increased. Therefore, the CIRC model can be considered an effective instructional strategy to enhance students' understanding and writing ability in descriptive texts